Gymnastics - Joseph, Paul, 1970- (Edina, Minn. : Abdo & Daughters, 1996)
Gives a basic introduction to gymnastics, including a brief history of the sport and descriptions of essential exercises.
Includes index.
Keywords: Gymnastics -- Juvenile literature; Gymnastics